Multicasting challenges in wireless mesh networks - Sanni, Mistura L.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Daoud, Jamal Ibrahim (IIUM Press, 2011)
The upsurge in the deployment of Wireless Mesh Networks (WMNs) is incident on the availability of portable devices requiring Internet facilities for group content distribution. It is an ad hoc network with broadband capability and low deployment cost. The application areas include academia and the industry, especially in situations where existing infrastructure is damaged due to natural disasters or even non-existence like rural areas and developing countries [1].